2021
DOI: 10.21307/ane-2021-003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vitamin E on neurodegenerative diseases: an update

Abstract: Vitamin E deficiency is associated with many neurological problems. Although the mechanisms of vitamin E action in neurodegenerative diseases are not clear, there are many possible mechanisms. Examples of such mechanisms are the protective effects of vitamin E against oxidative stress damage and its suppressive role in the expression of many genes involved in the development of neurodegeneration. Many studies have evaluated the relationship between vitamin E intake or vitamin E levels in body fluids and neurod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 114 publications
(137 reference statements)
0
8
0
Order By: Relevance
“…172 Many studies have demonstrated that VE can prevent neurodegenerative disorders such as Alzheimer's disease (AD) and Parkinson's disease (PD) can both be prevented by VE. 173,174 Mounting evidence suggests that patients with autism have low methylation ability and increased production of reactive oxygen species (ROS). In a postmortem study of brain tissues, patients with autism reported higher levels of oxidative stress biomarkers than healthy controls.…”
Section: Vitamin Ementioning
confidence: 99%
“…172 Many studies have demonstrated that VE can prevent neurodegenerative disorders such as Alzheimer's disease (AD) and Parkinson's disease (PD) can both be prevented by VE. 173,174 Mounting evidence suggests that patients with autism have low methylation ability and increased production of reactive oxygen species (ROS). In a postmortem study of brain tissues, patients with autism reported higher levels of oxidative stress biomarkers than healthy controls.…”
Section: Vitamin Ementioning
confidence: 99%
“…Being the most abundant form of vitamin E, α-tocopherol is found in dietary sources such as vegetable oils, nuts, and seeds. Vitamin E has been shown to exert antioxidant and anti-inflammatory properties that may potentially provide protective effects against neurodegeneration [111,112]. Patients with AD have lower circulating levels of vitamin E in cerebrospinal fluid (CSF) [70] and serum [71].…”
Section: Vitamin Ementioning
confidence: 99%
“…[ 94 , 95 ]. Although vitamin E is known for its antioxidative characteristics, due to its ability to scavenge the peroxyl radicals (ROO • ), thus inhibiting lipid peroxidation [ 94 , 95 , 96 ], data indicating vitamin E efficacy in neurodegenerative diseases such as AD, PD, stroke and ALS are inconclusive [ 97 , 98 ]. The results from the preclinical studies of its use for AMD prevention are also indecisive.…”
Section: Age-related Macular Degenerationmentioning
confidence: 99%